ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT Areca catechu L. Stalk USING THE DPPH METHOD - Tunnazilah, Nurhikmah; Arum Astuti, Ratih; Hardia, Lukman (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
A monocotyledonous plant from the wild palm group, the areca nut (Areca actechu L.), has numerous health advantages. Most people in Sorong City empirically cure illnesses with areca nut medication. Using the DPPH (2,2 diphenyl-1-picrylhydrazyl) technique, the secondary metabolite chemicals and antioxidant activity were determined. The areca palm stalks were extracted using a maceration method with a 96% ethanol filter. The IC50 value was used to test for antioxidants using UV-Vis spectrophotometry. Phytochemical analysis revealed that the areca stem extract contained tannins, alkaloids, steroids, and flavonoids.The results of the antioxidant activity test of areca nut stalk extract showed that the IC50 value in replication 1 was 32.66µg/mL, replication 2 was 32.88µg/mL, and replication 3 was 32.84 µg/mL. Conclusion: Ethanol extract of areca stalk (Areca catechu L.) has secondary metabolite compounds and antioxidant activity with an average IC50 value of mean ± SD = 32,79 ± 0,114. Keywords: antioxidants, dpph method, Areca catechu L.